Analisis Extranous Cognitive Load Buku Ajar Kurikulum Merdeka Kelas VIII Pada Materi Persamaan Garis Lurus - Nidya Ferry Wulandari (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2025)
Extraneous cognitive load will arise if the learning materials used are not integrated each other so that it will distract students' attention. This study aimed to analyze the quality of Merdeka curriculum textbook based on the principles of learning materials and multimedia features. The method used is qualitative research with content analysis. The results of this study are that the learning materials on linear equations in the Merdeka curriculum textbook have met the segmentation principle and the elements or illustrations and unimportant texts do not need to be presented in this materials. Some still meet the principle of using supporting images, diagrams, or illustrations and only some present integrated text and image information each other. The learning materials on linear equations still do not meet the pre-training principle. In terms of multimedia learning features, it is in accordance with the coherence, visual signaling features, some meet the principles of spatial contiguity and multimedia, but do not meet the redundancy, temporal contiguity, modality, and personalization, voice, and image features.